Implications of quantitative susceptibility mapping at 7 Tesla MRI for microbleeds detection in cerebral small vessel disease - Perosa, Valentina; Rotta, Johanna; Yakupov, Renat; Kuijf, Hugo J.; Schreiber, Frank; Oltmer, Jan T.; Mattern, Hendrik; Heinze, Hans-Jochen; Düzel, Emrah; Schreiber, Stefanie (Frontiers in Neurology, 2023)
Background: Cerebral microbleeds (MBs) are a hallmark of cerebral small vessel disease (CSVD) and can be found on T2*-weighted sequences on MRI. Quantitative susceptibility mapping (QSM) is a postprocessing method that also enables MBs identification and furthermore allows to differentiate them from calcifications. Aims: We explored the implications of using QSM at submillimeter resolution for MBs detection in CSVD. Methods: Both 3 and 7 Tesla (T) MRI were performed in elderly participants without MBs and patients with CSVD. MBs were quantified on T2*-weighted imaging and QSM. Differences in the number of MBs were assessed, and subjects were classified in CSVD subgroups or controls both on 3T T2*-weighted imaging and 7T QSM. Results: 48 participants (mean age [SD] 70.9[8.8] years, 48% females) were included: 31 were healthy controls, 6 probable cerebral amyloid angiopathy [CAA], 9 mixed CSVD, and 2 were hypertensive arteriopathy [HA] patients. After accounting for the higher number of MBs detected at 7T QSM (Median = Mdn; Mdn7T QSM = 2.5; Mdn3T T2* = 0; z = 4.90; p < 0.001) and false positive MBs (6.1% calcifications), most healthy controls (80.6%) demonstrated at least one MB and more MBs were discovered in the CSVD group. Conclusions: Our observations suggest that QSM at submillimeter resolution improves the detection of MBs in the elderly human brain. A higher prevalence of MBs than so far known in healthy elderly was revealed.